Impact of Change in Structure of Government on Health Service Delivery: A Case Study of Dang District of Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Nepal has changed its structure of governance from a centralized into decentralized system to improve its health service delivery to people. This paper aims to highlight the impact of this changed structure in health service delivery during this transition phase. Thus a cross sectional study was performed to study the impact, where semi-structured interviews in Nepali with officials of different health institutions under different tiers of government was conducted.MATERIALS AND METHODS: An input-process-output framework was applied to study the components of health service delivery. The data obtained was transcribed into English language and content analysis was executed under several headings.RESULTS: After analyzing the findings, mixed impact was observed with various challenges and opportunities in the way ahead for improving the health service delivery. A positive impact on the physical infrastructure was seen along with opportunities as well as challenges in human resource procurement. Management of budget as well as logistics have become difficult. Plan as suitable as possible are being made meanwhile, organizing the health system is becoming haphazard. Staff management along with training them and coordination among agencies have become more tedious. However a good outcome was present in aspects of service utilization and community participation.CONCLUSIONS: Nepal as a developing country has been making an effort in the way forward on improving its health service delivery and further research on this field is necessary. Also robust framework and policies to drive the country in delivering an improved health service is required.